Simulation of N+2 Logic for Amplifier in Railway Public Address System - Rosli, Nurul Asniena; Karthigesu Nagarajoo; Beant Singh Devinder Singh (Progress in Engineering Application and Technology, 2022)
An announcement becomes impossible if the public address (PA) system fails owing to equipment deterioration or a worker’s error during construction. In this project, a study has been conducted to improve current system to provide better availability by adding two additional spare channels to the system. The amplifiers and speaker buses of the PA system are used to make the announcement. Nonetheless, the existing approach, known as N+1 redundancy, can only handle one amplifier output failure at a time. Audio announcements cannot be played from the PA system to the affected zone as long as there is more than one amplifier output channel issue. This study provides a better approach of dealing with amplifier failure. The previous approach, N+1 Switch Protection, can still be used to transfer the input to the backup channel, but in this project, the current system will be improved to accommodate a better availability of redundancy using two spare channels. This strategy improves system availability while decreasing the frequency of amplifier maintenance by adding another spare channel to accommodate N+2 redundancy. This will allow maintenance employees to repair faults in a shorter time without disrupting PA system operation during operational hours, as well as reduce the frequency of amplifier maintenance service